2016
DOI: 10.7567/jjap.55.04em08
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity extended-gate field-effect transistors as pH sensors with oxygen-modified reduced graphene oxide films coated on different reverse-pyramid silicon structures as sensing heads

Abstract: A high-performance extended-gate field-effect transistor (EGFET) as pH sensor with its microstructured sensing head composed of an oxygen-modified reduced graphene oxide film (RGOF) on a reverse-pyramid (RP) Si structure was developed to achieve a high sensitivity of 57.5 mV/pH with an excellent linearity of 0.9929 in a wide pH sensing range of 1–13. These features were ascribed to the large amount of sensing sites and large sensing area. In contrast, the planar Si substrate with the oxygen-plasma-treated RGOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The normalized resistance (ΔR/R0) to the rGO resistance in air (R0 ~6.7 KΩ) decreased for unitary changes of pH from 3 to 8 with a sensitivity of 0. 4c) 104,105 . After spraying a commercial rGO solution onto the substrate and heating at 120 °C, the rGO was annealed in nitrogen at 300 °C for 1h and treated with oxygen plasma for 1 min.…”
Section: Reduced Graphene Oxidementioning
confidence: 99%
“…The normalized resistance (ΔR/R0) to the rGO resistance in air (R0 ~6.7 KΩ) decreased for unitary changes of pH from 3 to 8 with a sensitivity of 0. 4c) 104,105 . After spraying a commercial rGO solution onto the substrate and heating at 120 °C, the rGO was annealed in nitrogen at 300 °C for 1h and treated with oxygen plasma for 1 min.…”
Section: Reduced Graphene Oxidementioning
confidence: 99%
“…The 2D structure offered by the rGO layer is only confined to the solution interface on the FG by the SiO 2 insulator, which preserves the high surface-to-volume ratio for the sensing section. In contrast, it is challenging to avoid any influences of the bulk electrode underneath rGO layers for resistive connections of rGO layer , utilized in the conventional RGFET (Figure b) since the rGO layer is electrically coupled to the bulk electrode. That is, rGO and electrode complexes are regarded as a single combined resistor under the solution contact for a conventional RGFET, losing structural advantages offered by rGO layers at the solution interfaces.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Then, it was found that for the In addition, IR sensing [305,306], pH sensing [307,308] and ion sensing [262,309] of GObased FETs were also reported. Trung et al [305] demonstrated the IR sensing ability of RGO FETs, which exhibited high sensitivity and reproducibility even with a temperature interval of 1 K. Then, high pH sensitivity of 57.5 mV/pH and excellent linearity of 0.9929 in a wide pH sensing range of 1-13 were achieved in the RGO-based FETs using an oxygen plasma treatment to increase the functional groups on the RGO films [308]. Besides, high sensitivity and excellent lower detection limit of 1 nM for real-time detection of Hg 2+ in an underwater environment were also obtained in the RGO-based FETs [262].…”
Section: Field-effect Transistors (Fets)mentioning
confidence: 99%